Effects of Feed Species and HUFA Composition on Survival and Growth of the Longsnout Seahorse (Hippocampus reidi) - Schubert, Patrick; Vogt, Lena; Eder, Klaus; Hauffe, Torsten; Wilke, Thomas (Frontiers in Marine Science, 2016)
Globally, wild seahorse populations are threatened due to, habitat destruction and unsustainable human exploitation among others. Furthermore, aquaculture-based mass-scale rearing is still uncommon due to the low survival rates of seahorse juveniles and exceptionally high feed costs. Previous studies have demonstrated the importance of both highly unsaturated fatty acid (HUFA) supplies and a copepod-based rearing for seahorse survival and growth. As the latter is expensive, the question arises as to how high survival rates of seahorse juveniles can be assured under low- to moderate-cost feed regimes. In particular, it remains unknown whether the diet species or their dietary HUFA profiles determine the successful development of seahorse fry. Therefore, the aims of this study were to assess the dependence of growth and survival rates of Hippocampus reidi brood on the animal feed and to infer the impact of feed species vs. dietary HUFA profiles on juvenile growth. A nutrition experiment was conducted where juveniles were treated either with enriched Artemia nauplii (low-cost diet Art) or with a mixed diet of Artemia and copepods (moderate-cost diet Art/Cop). Larval survival and growth were analyzed using Cox proportional-hazard and mixed linear model analyses. We found that i) both diets enabled good survival, ii) diet Art/Cop resulted in superior weight and height growth, and iii) the differential effects of diets Art/Cop and Art cannot be explained by their different HUFA compositions alone. From an economical point of view, our findings of high survival rates and relatively high growth rates with the medium-cost treatment Art/Cop may open new possibilities for the large-scale rearing of seahorses. Even the application of a low-cost Art diet might be appropriate for seahorse aquacultures as both survival and growth rates are only marginally lower compared to the former diet.